Sequence-specific synthesis of macromolecules using DNA-templated chemistry. - Milnes, P; Mckee, M; Bath, J; Song, L; Stulz, E; Turberfield, A; O'Reilly, R (2012)
Using a strand exchange mechanism we have prepared, by DNA templated chemistry, two 10-mers with defined and tunable monomer sequences. An optimized reaction protocol achieves 85% coupling yield per step, demonstrating that DNA-templated chemistry is a powerful tool for the synthesis of macromolecules with full sequence control.